Criminal Cases are regulated in the Criminal Code, which is linked to the Principle of Legality in Criminal Law. - Nia Ayu Mayang Sari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2026)
This study analyzes that criminal law in Indonesia is fundamentally governed by the Criminal Code (Kitab Undang-Undang Hukum Pidana/ KUHP) as the primary legal framework that defines criminal acts and determines the sanctions that may be imposed by the state. The central principle within this criminal law system is the Principle of Legality, as stipulated in Article 1 paragraph (1) of the KUHP, which affirms that no act may be subject to criminal punishment without a prior statutory basis. This study aims to examine the regulation of criminal cases under the KUHP and to analyze the implementation of the Principle of Legality in the practice of criminal law enforcement in Indonesia. The research employs a normative legal method using statutory, conceptual, and doctrinal approaches to examine relevant legal norms and principles. The Principle of Legality plays an important role in ensuring legal certainty, protecting human rights, and preventing arbitrary actions by law enforcement authorities. However, its implementation faces challenges, particularly in responding to the development of new forms of crime that are not explicitly regulated in the KUHP. Therefore, this study emphasizes the importance of continuous and adaptive criminal law reform while maintaining consistency with the Principle of Legality in order to achieve a fair criminal justice system.